Knowledge, Attitude and Practice of Hand Hygiene among Medical Students of CIMS Multan, Pakistan - Ghazal Farrukh, Farhan Ahmed, Muhammad Ali, Aasma Ismail, Hafiza Qurat-Ul-Ain, Ahsan Rashid Rana, Hafiz Muhammad Abdullah, Abir Ishtiaq, Muhammad Khalid, Sheikh Muhammad Azam, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: One of the most crucial methods for preventing the spread of infections in the health care system is hand hygiene (HH). Health Care Professionals (HCPs) place a high value on HH knowledge, attitude, and practice, and non-compliance may have unfavorable effects. Objectives: This study, which is being conducted at the CMH Multan Institute of Medical Sciences (CIMS), Multan, Pakistan (PK), aims to evaluate and compare the knowledge, attitude, and practice of medical students in their clinical year, interns, and between male and female students while also identifying knowledge gaps. Methods: This study was cross-sectional in nature. 188 medical apprentices and students enrolled in the clinical year (99 men and 89 women). From the beginning of February 2022 till June 2022, five months, this study was finished. The standard self-structured hand hygiene (HH) questionnaire was utilized, and Statistical Package for the Social Sciences (SPSS-20) was used to analyze the results. Results: 188 students overall, both male and female, responded to the survey. About 92% (173 out of 188) of the responders were in the 18–24 age range. In general, it was discovered that clinical year medical students at CIMS, Multan, Pakistan, had a moderate level of knowledge, attitude, and behaviors about hand cleanliness (50% -75%). In terms of HH, female participants had better attitudes and knowledge than male participants (i.e., >75%), but there was no difference in terms of practice. Conclusion: Concerning hand hygiene, there are ‘overall’ satisfactory knowledge, attitude and practice towards HH. Future research in this field should focus on both self- reported responses and directly observed data to assess the practical application of good hand hygiene practices. Keywords: Hand hygiene; Knowledge; Attitude; Practice; Medical students; Self-structured Questionnaire.